A new method for the determination of naphatylamines in workplace air for occupational exposure assessment - Anna Jeżewska; Dorota Kondej; Agnieszka Woźnica (Nofer Institute of Occupational Medicine, 2021)
Background Naphthylamine (NA), i.e., 1-naphthylamine (1-NA) and 2-naphthylamine (2-NA) and its salts (2-naphthylamine hydrochloride and 2-naphthylamine acetate) are colorless crystalline solids. They have been used, among others, in the production of paints and dyes. In the European Union, 1-NA is classified as a toxic substance, and 2-NA and its salts as carcinogenic category 1A. The aim of this study was to develop a new method for the determination of NA, which will enable the determination of 1-NA and 2-NA and its salts in the working environment, in the concentration range of 0.3-6 μg/m 3 . Material and Methods The method consists in passing the test air containing the substances to be determined through a glass fiber filter impregnated with sulphuric acid(VI). After recovery with water and sodium hydroxide solution followed by extraction into a solid on Oasis HLB columns, the solutions in methanol are analyzed using a high-performance liquid chromatograph with a fluorescence detector and Ultra C18 column. Results The method developed allows determining 1-NA and 2-NA and its salts in the concentration range of 0.3-6 μg/m 3 . The limit of detection for 1-NA is 81 pg/ml and for 2-NA - 80.6 pg/ml. Conclusions The method is characterized by good precision and accuracy; it meets the requirements of European Standard PN-EN 482 and can be used by occupational hygiene laboratories to measure the level of 1-NA and 2-NA and its salts in workplace air to assess workers' exposure to these substances. Med Pr. 2021;72(2):145-54